Students' Perceptions of Digital Literacy Toward Historical Content on TikTok and YouTube Among Grade XI Students at SMA Negeri 7 Semarang - Diva Putri Prahesti; Romadi Romadi (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
The advancement of digital technology has encouraged Generation Z students to use TikTok and YouTube as history learning resources; however, their digital literacy skills in evaluating such content remain understudied. This study aims to analyze the perceptions of eleventh-grade students at SMA Negeri 7 Semarang regarding digital literacy in accessing historical content on TikTok and YouTube. A mixed methods approach with a sequential explanatory design was employed, collecting data through a Likert-scale questionnaire (1–5) distributed to 65 respondents, followed by in-depth interviews with eight informants. The instrument was developed based on four digital literacy competencies proposed by Paul Gilster: internet searching, hypertextual navigation, content evaluation, and knowledge assembly. The findings indicate that students' overall digital literacy falls into the moderate category with a mean score of 3.46 (69.18%). Internet searching (3.54) and knowledge assembly (3.53) were relatively stronger, whereas hypertextual navigation (3.35) and content evaluation (3.44) remained lower. Students perceived historical content on social media as more engaging due to visual and animated presentations; however, their ability to assess source credibility was still superficial. It is concluded that students' digital literacy needs further improvement, particularly in hypertextual navigation and content evaluation, so that they can critically utilize social media in history learning.